2021
DOI: 10.3389/fpsyg.2021.668049
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between the 5Cs and Anxiety—Insights From Three Countries: Portugal, Slovenia, and Spain

Abstract: Several of the most frequent psychological difficulties in childhood and adolescence are related to anxiety and lead to numerous short- and long-term negative outcomes in emotional, social, and academic domains. Empirical evidence consistently shows that the 5Cs (competence, caring, confidence, connection, and character) of Positive Youth Development (PYD) are positively related to adolescents’ contribution to self, family, and society as well as negatively related to risky behaviors and emotional difficulties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 48 publications
(72 reference statements)
0
14
0
Order By: Relevance
“…Geldhof et al (2019) showed that Caring was positively associated with depression, concluding that "young people may suffer if they care too much" (p.1) and this dimension should grow adaptive developmental regulations with the context in order to lead to positive outcomes. In this same line, Caring was found to be positively related to other problems in mental health, such as anxiety (Kozina et al, 2021). Moreover, the dimension of Character, defined as respect for the rules of the society, is strongly and positively correlated with Caring.…”
Section: Negative Relationships Between Positive Youth Development and Depression Controlling For Country And Gendermentioning
confidence: 71%
“…Geldhof et al (2019) showed that Caring was positively associated with depression, concluding that "young people may suffer if they care too much" (p.1) and this dimension should grow adaptive developmental regulations with the context in order to lead to positive outcomes. In this same line, Caring was found to be positively related to other problems in mental health, such as anxiety (Kozina et al, 2021). Moreover, the dimension of Character, defined as respect for the rules of the society, is strongly and positively correlated with Caring.…”
Section: Negative Relationships Between Positive Youth Development and Depression Controlling For Country And Gendermentioning
confidence: 71%
“…For the case of caring, this suggests that being too concerned, over-empathic or over-invested in others might result in negative effects on own mental health. For character, the concern with following rules and being evaluated by others have been discussed as elements that explain the relationship with anxiety (Kozina et al, 2021). As previously Geldhof et al (2019) the mechanisms that underlie these observations need to be further examined.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to potentially less favorable consequences of having high scores on these constructs. For example, previous studies have shown that higher scores on caring (Holsen et al, 2017;Geldhof et al, 2019;Kozina et al, 2021), and character (Kozina et al, 2021) dimensions were associated with higher levels of symptoms of anxiety and depression. For the case of caring, this suggests that being too concerned, over-empathic or over-invested in others might result in negative effects on own mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous research on internalizing behaviors, such as depression and anxiety, we expect to find a negative association between Character, Competence, Connection and Confidence and depressive symptoms [ 15 , 47 ] and a positive association between Caring and depressive symptoms [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%